2021
DOI: 10.1111/jems.12466
|View full text |Cite
|
Sign up to set email alerts
|

Behavior‐based price discrimination with nonuniform distribution of consumer preferences

Abstract: Firms commonly price discriminate across consumers based on purchase history, a practice known as behavior-based price discrimination (BBPD). Existing studies usually assume that consumer preferences follow uniform distribution, and find that BBPD benefits consumers at the cost of firms, prisoners' dilemma. In this paper, we consider a class of consumer preferences distribution and show that new profit and welfare results arise. In particular, when consumer preferences are sufficiently clustered at the center … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Esteves, 2009b) 3 or imperfect targetability (Chen et al, 2001). 4 In dynamic settings, pro…ts may increase with BBPD due to imperfect correlated preferences across time (Chen andPearcy, 2010, andShin andSudhir, 2010), consumers'demand heterogeneity (Shin and Sudhir, 2010), heterogeneity in price sensitivity (Colombo, 2018), nonuniform distribution of consumer preferences (Esteves et al, 2020), imperfect informed consumers (Chen and Zhang 2009, Esteves, 2009a, and Esteves and Resende, 2016.…”
Section: Relevant Literaturementioning
confidence: 99%
“…Esteves, 2009b) 3 or imperfect targetability (Chen et al, 2001). 4 In dynamic settings, pro…ts may increase with BBPD due to imperfect correlated preferences across time (Chen andPearcy, 2010, andShin andSudhir, 2010), consumers'demand heterogeneity (Shin and Sudhir, 2010), heterogeneity in price sensitivity (Colombo, 2018), nonuniform distribution of consumer preferences (Esteves et al, 2020), imperfect informed consumers (Chen and Zhang 2009, Esteves, 2009a, and Esteves and Resende, 2016.…”
Section: Relevant Literaturementioning
confidence: 99%
“…However, when both manufacturers and retailers employ BBP, it results in an increase in profits for channel members and a decrease in consumer surplus. Esteves et al (2022) assessed whether price discrimination based on purchasing history benefit/harm industry profits and consumers in markets where the density of consumer preferences is nonuniform; they showed that when consumers are sufficiently massed at the center of the market, BBPD boosts industry profits at the expense of consumers. Ma et al (2023) examined information disclosure strategies and BBPD strategies within horizontal competition channels.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Finally, we discuss the distribution of the consumers. As in Esteves et al [2022], we assume the following non-uniform distribution, with f (x) being the density function of the cumulative distribution function F(x) over the support x ∈ [0, 1]:…”
Section: The Modelmentioning
confidence: 99%
“…As in Esteves et al . [2022], we assume the following non‐uniform distribution, with f ( x ) being the density function of the cumulative distribution function F ( x ) over the support x[0,1]$$ x\in \left[0,1\right] $$: f(x)goodbreak={4βxgoodbreak+(1goodbreak−β)italicif0.5emx[0,1false/2]4β(1goodbreak−x)goodbreak+(1goodbreak−β)italicif0.5emx(1false/2,1].$$ f(x)=\left\{\begin{array}{cc}4\beta x+\left(1-\beta \right)& if\kern0.5em x\in \left[0,1/2\right]\\ {}4\beta \left(1-x\right)+\left(1-\beta \right)& if\kern0.5em x\in \left(1/2,1\right]\end{array}\right.. $$ Parameter β[β_,1]$$ \beta \in \left[-\underset{\_}{\beta },1\right] $$, with β_=(35)false/2$$ \underset{\_}{\beta }=\left(3-\sqrt{5}\right)/2 $$, is half the difference between the density of the endpoints of the market and the centre, that is β=f(1false/2)f(0)2=f(1false/2)f(1)2$$ \beta =\frac{f\left(1/2\right)-f(0)}{2}=\frac{f\left(1/2\right)-f(1)}{2} $$. Note that the distribution is symmetric around …”
Section: The Modelmentioning
confidence: 99%
See 1 more Smart Citation